Spallation of 56Fe by 1.0 GeV Protons - Nicolis, N. G.; Souliotis, G. S.; Asimakopoulou, A. (HNPS Advances in Nuclear Physics, 2019)
Mass, charge and isotopic distributions observed in spallation reactions of 56Fe with 1 GeV protons are analysed in the framework of the intranuclear cascade code ISABEL coupled with the sequential binary decay code MECO. The code MECO provides a description of the equilibrated nuclear decay by the emission of gamma-rays, light-mass particles and clusters as well as intermediate mass fragments emitted in their ground, excited bound and excited unbound states (continuum) according to a generalized Weisskopf formalism. A good overall description of the experimental data is obtained with a global Fermi gas level density parameter and inverse cross sections based on the Christensen and Winther nuclear potential. Multifragmentation decay events are simulated with the code SMM and their influence on the above observables is discussed.